Sepsis in patients who are immunocompromised: diagnostic challenges and future therapies - Deinhardt-Emmer, Stefanie; Chousterman, Benjamin G; Schefold, Joerg C; Flohé, Stefanie B; Skirecki, Tomasz; Kox, Matthijs; Winkler, Martin S; Cossarizza, Andrea; Wiersinga, W Joost; van der Poll, Tom; Weigand, Markus A.; Cajander, Sara; et al. (The lancet. Respiratory medicine, 2025)
Sepsis is a life-threatening, dysregulated host response to infection. Immunosuppression is a risk factor for infections and sepsis. However, the specific immune derangements elevating the risk for infections and sepsis remain unclear in the individual patient, raising the question of whether a general state of immunosuppression exists. In this Review, we explore the relationship between immunosuppression and sepsis, detailing the definitions, causes, and clinical implications. We address the effect of primary immunodeficiencies, acquired conditions, and drugs on the risk of infection and the development of sepsis. Patients with sepsis who are immunocompromised often present with atypical symptoms and diagnostic test results can differ, making early recognition difficult. Future perspectives entail novel biomarkers to improve early sepsis detection and tailored treatments to modulate immune function. Including patients who are immunocompromised in clinical trials is crucial to enhance the relevance of research findings and improve treatment strategies for this vulnerable population.